2016
DOI: 10.1159/000443438
|View full text |Cite
|
Sign up to set email alerts
|

Salt Sensitivity Determined From Capillary Blood

Abstract: Background/Aims: A significant rise of blood pressure in response to a given salt load is a weak indication of high salt sensitivity, supposed to foster the development of arterial hypertension and related diseases in later life. In search of an alternative method we recently developed the salt blood test (SBT), a new concept for quantifying salt sensitivity (SS). Based on this concept, namely that red blood cells (RBC) report on salt sensitivity, the SBT-mini was developed. Methods: The SBT-mini utilizes a dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…Individuals with meaningful BP increases or decreases following increases or decreases in salt intake, respectively, are termed salt sensitive while those who do not exhibit such changes in BP are called salt resistant [ 14 ]. Thus, BP in salt sensitive individuals correlates positively with salt intake and ESS [ 4 , 6 , 13 ]. Although we did not compare BP values with ESS, it has been reported that excess salt intake has pathological effects on the buffering capacity and function of the vasculature that are independent of BP [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Individuals with meaningful BP increases or decreases following increases or decreases in salt intake, respectively, are termed salt sensitive while those who do not exhibit such changes in BP are called salt resistant [ 14 ]. Thus, BP in salt sensitive individuals correlates positively with salt intake and ESS [ 4 , 6 , 13 ]. Although we did not compare BP values with ESS, it has been reported that excess salt intake has pathological effects on the buffering capacity and function of the vasculature that are independent of BP [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a separate study, a low erythrocyte buffering capacity (high ESS) correlated with higher blood pressure [ 6 ]. Because red blood cells play an important role in buffering sodium ions [ 5 , 6 ], it is expected that red blood cell count correlates inversely with ESS and our study confirmed this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This now commercially available assay could easily be integrated in the clinical workup before planning RDN. As described by the developer of the SBT, the erythrocyte sodium sensitivity (ESS), and the red blood cells (RBC) sodium buffer capacity does correspond to the patients’ individual salt sensitivity ( 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%